2015
DOI: 10.1002/anie.201503869
|View full text |Cite
|
Sign up to set email alerts
|

An Activity‐Based Probe for Studying Crosslinking in Live Bacteria

Abstract: Penicillin-binding proteins (PBPs) catalyze the crosslinking of peptidoglycan (PG), an essential process for bacterial growth and survival, and a common antibiotic target. Yet, despite its importance, little is known about the spatiotemporal aspects of crosslinking—largely because of a lack of experimental tools for studying the reaction in live bacteria. Here we introduce such a tool: an activity-based probe that enables visualization and relative quantitation of crosslinking in vivo. In Staphylococcus aureus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 31 publications
0
31
0
Order By: Relevance
“…5052 Prior studies have demonstrated that structural mimicry of nascent PBP substrates results in PG incorporation in vitro (53) and in live bacterial cells. 54,55 Also, during the preparation of our manuscript it was shown, in vitro , that Ldts mediate cross-linking of synthetic Ldt substrates. 56 In contrast, there are currently no Ldt-specific probes to tag and visualize Ldt activity in live cells.…”
mentioning
confidence: 84%
“…5052 Prior studies have demonstrated that structural mimicry of nascent PBP substrates results in PG incorporation in vitro (53) and in live bacterial cells. 54,55 Also, during the preparation of our manuscript it was shown, in vitro , that Ldts mediate cross-linking of synthetic Ldt substrates. 56 In contrast, there are currently no Ldt-specific probes to tag and visualize Ldt activity in live cells.…”
mentioning
confidence: 84%
“…The potency of the organic guanidine single crystals exposed to antibacterial drug was evaluated against two pathogenic bacterial strains. The biological activities of the Guanidine derivatives have been studied for its antibacterial activities using disk diffusion method 10 13 also confirmed the antibacterial activity of S. aerus against 2-Chloro-5-Ethoxy-3,6-Bis(Methylamino)-1,4-Benzoquinone single crystals. The activity of the Guanidine compounds towards Bacillus subtilis decreases in the order GuAce > GuAcr > Gutfb = Kanamycin > Guhtt= Gumal.…”
Section: Resultsmentioning
confidence: 74%
“…The antibacterial activity of the Guanidine derivatives.The Guanidine maleate and Guanidine tartarate shows a minimum activity against Bacillus subtilis bacteria and Guanidine tetrafluroborate shows the low activity against Staphylococcus aerus pathogen. The Guanidine derivatives with malaete and tartarate have less antibacterial activity against B. subtilis; and Guanidine derivatives with tetrafluroborate have less activity against S. aerus Gautam et al 2015. …”
mentioning
confidence: 98%
“…Scientists are still looking for probes targeting glycine cross-bridges (94), the membrane anchor of lipid II, or even the probes that can distinguish 3–3 and 3–4 cross-linking in PG. The search for novel PG probes will undoubtedly continue to be a very active area of research.…”
Section: Discussion and Future Directions In Visualization Of Peptidomentioning
confidence: 99%